2022
DOI: 10.1371/journal.pcbi.1010785
|View full text |Cite
|
Sign up to set email alerts
|

The catecholamine precursor Tyrosine reduces autonomic arousal and decreases decision thresholds in reinforcement learning and temporal discounting

Abstract: Supplementation with the catecholamine precursor L-Tyrosine might enhance cognitive performance, but overall findings are mixed. Here, we investigate the effect of a single dose of tyrosine (2g) vs. placebo on two catecholamine-dependent trans-diagnostic traits: model-based control during reinforcement learning (2-step task) and temporal discounting, using a double-blind, placebo-controlled, within-subject design (n = 28 healthy male participants). We leveraged drift diffusion models in a hierarchical Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 130 publications
3
13
0
Order By: Relevance
“…Therefore, one could speculate that an increase in overall uncertainty and concomitant dopamine release [67], combined with a potentially general increase in dopamine levels in the gambling group [70] might underlie the observed effects. In line wth this interpretation, decision threholds / boundary separation parameters were reduced by pharmacologically increasing dopamine levels using the same task reported here [41], and the dopamine precursor tyrosine reduced decision thresholds across two different decision-making tasks [71].…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, one could speculate that an increase in overall uncertainty and concomitant dopamine release [67], combined with a potentially general increase in dopamine levels in the gambling group [70] might underlie the observed effects. In line wth this interpretation, decision threholds / boundary separation parameters were reduced by pharmacologically increasing dopamine levels using the same task reported here [41], and the dopamine precursor tyrosine reduced decision thresholds across two different decision-making tasks [71].…”
Section: Discussionsupporting
confidence: 67%
“…The absence of an effect of Levodopa in the sham stimulation condition is consistent with previous findings showing evidence for no effect of dopamine drug manipulations on either response caution or discriminability in simple decisionmaking tasks (e.g., Winkel et al, 2012). Dopamine drug manipulations seem to only alter response caution or discriminability under specific circumstances: for example when decision-making was embedded within paradigms requiring proactive inhibition (Rawji et al, 2020), reinforcement learning (Chakroun et al, 2022;Mathar et al, 2022), or temporal discounting (Wagner et al, 2020), or only in clinical populations with impaired dopamine function and decision-making behaviour (Huang et al, 2015;Wagner et al, 2020). Studies which have found effects of dopamine drug manipulations on the speed-accuracy trade-off ((e.g., Pedersen et al, 2017;Beste et al, 2018;Bensmann et al, 2019) have used methylphenidate, a drug that works by blocking the re-uptake of dopamine and noradrenaline, resulting in increased dopamine levels in both frontal cortex (Claussen & Dafny, 2014) and the basal ganglia (Westbrook et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies that examined drug effects on changes in discounting (Mathar et al, 2022;Peters & D'Esposito, 2020;Wagner et al, 2020)…”
Section: 𝜅 = 𝜅supporting
confidence: 89%
“…In this model, the SV of the HC option and the SV of the LC option are calculated separately. Once again, R t denotes the corresponding reward magnitude, and E t represents the associated effort in percentage on trial t. Consistent with previous studies that examined drug effects on changes in discounting (Mathar et al, 2022; Peters & D’Esposito, 2020; Wagner et al, 2020), we extended the original single-parameter model by incorporating two additional free parameters (Eq. 4).…”
Section: Methodsmentioning
confidence: 99%